The Impact of Outside Funds and Consumer Lending Against Profitability Return On Asset (ROA) For the Years 2012 Through 2021 at Bank BJB - Rahayu, Yayu (Fakultas Ekonomi Universitas Garut, 2023)
The aim of this investigation was to discover 1) the results of external financing (DPK) on return on asset (ROA) profitability. 2) How is the result of consumer lending on return on asset (ROA) profitability? 3) How is the impact of external financing (DPK) and consumer financing on return on asset (ROA) profitability? The study's research methodology is the quantitative descriptive approach method. Participants in this study are all of Bank BJB's financial statements from its establishment through 2021. The data gathering technique was completed through a literature review a documentation study. Multiple linear regression is employed to analyze the data analysis. This investigation came to the conclusion that DPK has a favorable and important impact return on asset (ROA) profitability, partially consumer lending has a good and significant impact on return on asset (ROA) profitability, and then DPK and consumer lending together have an important and favorable impact on ROA profitability.